Narrative Review of the Pathogenesis of Stasis Dermatitis: An Inflammatory Skin Manifestation of Venous Hypertension - Jonathan Silverberg; J. Mark Jackson; Robert S. Kirsner; Roni Adiri; Gary Friedman; Xing-Hua Gao; Steven D. Billings; Urs Kerkmann (Adis, Springer Healthcare, 2023)
Plain Language Summary Stasis dermatitis is a skin disease that affects the legs, most often of older people, with chronic venous insufficiency. Chronic venous insufficiency is when veins cannot return blood from the legs back to the heart. This leads to high blood pressure in veins and causes blood in those veins to flow backwards. If stasis dermatitis is left untreated, complications, including skin ulcers, can result. Other skin symptoms of stasis dermatitis include itchiness, scaling, and discoloration. Such skin symptoms can have a negative effect on a person's quality of life. Inflammation that lasts a long time is likely the main link between the skin changes seen in people with stasis dermatitis and the increased pressure in leg veins. Several molecules are associated with the inflammation observed in stasis dermatitis, including white blood cells, matrix metalloproteinases, phosphodiesterase 4, and interleukin-31. Treatment for stasis dermatitis should focus both on the underlying chronic venous insufficiency and the associated skin issues. Identifying inflammatory markers and pathways could help treat the signs and symptoms associated with stasis dermatitis, including the skin symptoms.